Extracellular CIRP Induces Inflammation in Alveolar Type II Cells via TREM-1 - Tan, Chuyi; Gurien, Steven D.; Royster, William; Aziz, Monowar; Wang, Ping (Frontiers in Cell and Developmental Biology, 2020)
Extracellular cold-inducible RNA-binding protein (eCIRP) induces acute lung injury (ALI) in sepsis. Triggering receptor expressed on myeloid cells-1 (TREM-1) serves as a receptor for eCIRP to induce inflammation in macrophages and neutrophils. The effect of eCIRP on alveolar epithelial cells (AECs) remains unknown. We hypothesize that eCIRP induces inflammation in AECs through TREM-1. AECs were isolated from C57BL/6 mice and freshly isolated AECs were characterized as alveolar type II (ATII) cells by staining AECs with EpCAM, surfactant protein-C (SP-C), and T1 alpha (T1α) antibodies. AECs were stimulated with recombinant murine (rm) CIRP and assessed for TREM-1 by flow cytometry. ATII cells from WT and TREM-1-/- mice were stimulated with rmCIRP and assessed for interleukin-6 (IL-6) and chemokine (C-X-C motif) ligand 2 (CXCL2) in the culture supernatants. ATII cells from WT mice were pretreated with vehicle (PBS), M3 (TREM-1 antagonist), and LP17 (TREM-1 antagonist) and then after stimulating the cells with rmCIRP, IL-6 and CXCL2 levels in the culture supernatants were assessed. All of the freshly isolated AECs were ATII cells as they expressed EpCAM and SP-C, but not T1α (ATI cells marker). Treatment of ATII cells with rmCIRP significantly increased TREM-1 expression by 56% compared to PBS-treated ATII cells. Stimulation of WT ATII cells with rmCIRP increased IL-6 and CXCL2 expression, while the expression of IL-6 and CXCL2 in TREM-1-/- ATII cells were reduced by 14% and 23%, respectively. Pretreatment of ATII cells with M3 and LP17 significantly decreased the expression of IL-6 by 30%, and 47%, respectively and CXCL2 by 27%, and 34%, respectively, compared to vehicle treated ATII cells after stimulation with rmCIRP. Thus, eCIRP induces inflammation in ATII cells via TREM-1 which implicates a novel pathophysiology of eCIRP-induced ALI and directs a possible therapeutic approach targeting eCIRP-TREM-1 interaction to attenuate ALI.